18F-Choline PET/CT in Leptomeningeal Breast Cancer Metastases. (February 2019) - Cuppari, Lea; Reccia, Pasquale; Burei, Marta; Cervino, Anna Rita; Evangelista, Laura
Abstract : Abstract: We describe a case of 47-year-old woman affected by human epidermal growth factor receptor-2–positive breast cancer with a diffuse leptomeningeal carcinomatosis. An intense uptake of 18 F-choline was reported at fused PET/MRI images in the brain, compatible with a diffuse leptomeningeal disease. This case highlights that 18 F-choline PET would be used for the identification of leptomeningeal involvement in patients affected by breast cancer, as a support of MRI images.